Using captive sentinels to collect wild triatomines in the region of Marília-SP, Brasil - Martins, Luciamáre Perrinetti Alves; Castanho, Roberto Esteves Pires; Tonon, Felipe Frasão; Unterleider, Carlos Eduardo; Rosa, João Aristeu da [UNESP] (Universidade Federal de Goias, 2013)
In order to collect wild triatomines in the municipality of Marilia, two captive sentinel sites were installed in a remnant riparian zone in the Atlantic Forest comprising 34 hectares located on the Nossa Senhora Aparecida farm. One enclosure was built on the margin and another inside the forest, about 200 meters from the edge, using rabbits as bait to attract wild triatomines. In addition to the caged rabbits, active searches for triatomines were performed in tree holes, bird nests and armadillo burrows by spraying Pirisa 1080-L1E1 aerosol dislodger. The sentinels were maintained for one year and four months. During this period six active searches were performed, but without success in attracting or colonizing wild triatomines. One factor that has probably intervened in the triatomine colonization is the periodic application of insecticides formulated with pyrethroid in farms neighboring the forest to fight Diaphorina citri in orange plantations.

Com o objetivo de coletar triatomíneos silvestres na região do município de Marília foram instalados dois cativeiros experimentais em uma mata ciliar remanescente de Mata Atlântica, com 34 hectares de extensão localizada no sítio Nossa Senhora Aparecida. Um cativeiro foi construído às margens e outro no interior da mata a aproximadamente 200 metros da borda, utilizando-se coelhos como atrativos para triatomíneos silvestres. Além dos cativeiros experimentais foram realizadas buscas ativas de triatomíneos em ocos de árvores, ninhos de pássaros, habitáculos de tatu com pulverização do desalojante Pirisa 1080-L1E1. Os cativeiros foram mantidos por um ano e quatro meses e seisbuscas ativas foram realizadas nesse período, porém sem sucesso na colonização de triatomíneos silvestres. Um dos fatores que provavelmente tenham interferido para a não colonização de triatomíneos seja a aplicação periódica de inseticida a base de piretróide nas fazendas vizinhas da mata para combater o Diaphorina citri nas plantações de laranja.
Ensaio experimental para captura de triatomíneos silvestres na região de Marília-SP
Keywords: Trypanosoma cruzi; Wild triatomines; Pyrethroid; Captive sentinel; Diaphorina citri; Trypanosoma cruzi; Triatomíneos silvestres; Cativeiro experimental; Diaphorina citri